Wireshark Implementation to Monitor Security on Wifi Indihome - Rizki Ananta; Firmansyah Firmansyah; Muh. Fadli Hasa (Universitas Islam Al-Azhar Mataram, 2025)
The increasing use of wireless networks, such as Indihome WiFi, raises significant concerns regarding network security. Cyber threats like data theft, unauthorized access, and malware attacks can compromise user privacy and data integrity. Therefore, monitoring network traffic is essential to detect and mitigate potential security risks. This study explores the implementation of Wireshark, a widely used network protocol analyzer, to monitor security on Indihome WiFi networks. Wireshark enables real-time packet capture and analysis, allowing for the inspection of data traffic, detection of suspicious activities, and identification of vulnerabilities. This research focuses on analyzing network protocols, identifying anomalies such as unauthorized access attempts, and evaluating encryption effectiveness. The methodology involves capturing WiFi packets, filtering data based on protocols (e.g., TCP, UDP, HTTP), and analyzing potential security threats like ARP spoofing or DNS hijacking. The results indicate that Wireshark effectively detects irregular traffic patterns, unencrypted data transmissions, and potential intrusion attempts. However, its effectiveness depends on proper configuration and user expertise in interpreting packet data. The study concludes that Wireshark is a valuable tool for enhancing Indihome WiFi security but should be complemented with other security measures such as firewalls, strong encryption (e.g., WPA3), and regular network audits. Future research could explore automated threat detection integration with Wireshark to improve real-time response capabilities.